An OMERACT reliability exercise of inflammatory and structural abnormalities in patients with knee osteoarthritis using ultrasound assessment. Issue 5 (22nd April 2015) - Bruyn, George AW; Naredo, Esperanza; Damjanov, Nemanja; Bachta, Artur; Baudoin, Paul; Hammer, Hilde Berner; Lamers-Karnebeek, Femke BG; Moller Parera, Ingrid; Richards, Bethan; Taylor, Mihaela; Ben-Artzi, Ami; D'Agostino, Maria-Antonietta; et al.
Abstract : Objective: To assess whether ultrasonography (US) is reliable for the evaluation of inflammatory and structural abnormalities in patients with knee osteoarthritis (OA). Methods: Thirteen patients with early knee OA were examined by 11 experienced sonographers during 2 days. Dichotomous and semiquantitative scoring was performed on synovitis characteristics in various aspects of the knee joint. Semiquantitative scoring was done of osteophytes at the medial and lateral femorotibial joint space or cartilage damage of the trochlea and on medial meniscal damage bilaterally. Intra- and interobserver reliability were computed by use of unweighted and weighted κ coefficients. Results: Intra- and interobserver reliability scores were moderate to good for synovitis (mean κ 0.67 and 0.52, respectively) as well as moderate to good for the global synovitis (0.70 and 0.50, respectively). Mean intra- and interobserver reliability κ for cartilage damage, medial meniscal damage and osteophytes ranged from fair to good (0.55 and 0.34, 0.75 and 0.56, 0.73 and 0.60, respectively). Conclusions: Using a standardised protocol, dichotomous and semiquantitative US scoring of pathological changes in knee OA can be reliable.